2020
DOI: 10.1038/s41423-020-0381-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ACPA inhibits NET formation: a potential therapy for neutrophil-mediated inflammatory diseases

Abstract: Excessive release of neutrophil extracellular traps (NETs) is associated with disease severity and contributes to tissue injury, followed by severe organ damage. Pharmacological or genetic inhibition of NET release reduces pathology in multiple inflammatory disease models, indicating that NETs are potential therapeutic targets. Here, we demonstrate using a preclinical basket approach that our therapeutic anti-citrullinated protein antibody (tACPA) has broad therapeutic potential. Treatment with tACPA prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 94 publications
4
100
0
Order By: Relevance
“…Appealingly, a therapeutic ACPA design to alter the binding of ACPAs, by targeting citrulline at a specific position, was documented to suppress NETosis from human neutrophils triggered by disease-relevant stimuli [121]. The changes in the neutrophil response upon ACPA alteration again strengthen the importance of ACPAs in triggering NETosis [121].…”
Section: Acpa-forming Ics Promote Netosis and The Release Of Degradatmentioning
confidence: 99%
See 2 more Smart Citations
“…Appealingly, a therapeutic ACPA design to alter the binding of ACPAs, by targeting citrulline at a specific position, was documented to suppress NETosis from human neutrophils triggered by disease-relevant stimuli [121]. The changes in the neutrophil response upon ACPA alteration again strengthen the importance of ACPAs in triggering NETosis [121].…”
Section: Acpa-forming Ics Promote Netosis and The Release Of Degradatmentioning
confidence: 99%
“…Just as Khandpur and others discovered that NETosis was enhanced in neutrophils in RA synovial fluid and systemic circulation, sera extracted from RA patients, particularly those rich in ACPAs, were shown to significantly stimulate NETosis [101]. Appealingly, a therapeutic ACPA design to alter the binding of ACPAs, by targeting citrulline at a specific position, was documented to suppress NETosis from human neutrophils triggered by disease-relevant stimuli [121]. The changes in the neutrophil response upon ACPA alteration again strengthen the importance of ACPAs in triggering NETosis [121].…”
Section: Acpa-forming Ics Promote Netosis and The Release Of Degradatmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study has reported higher levels of NE in lung parenchyma, bronchoalveolar lavage fluid (BALF) and sera from patients with IPF when compared with those in normal subjects, suggesting an involvement of NE in the pathogenesis of IPF [ 33 ]. Furthermore, pharmacological inhibition of neutrophil extracellular trap formation may represent a promising therapy for the treatment of various inflammatory diseases [ 34 ].…”
Section: Innate Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
“…NETs, a network structure consisted of DNA and granulose, could indirectly impair the endothelial function,promote blood vessel and glomerular damage, thus it would induce renal failure and even death [21]. Several previous studies respectively reported that the imbalance between the emergence and removal of NETs adversely affected kidney health [22,23].…”
Section: Discussionmentioning
confidence: 99%